Epistasis Between Two Gene Variants of Leptin and Vascular Endothelial Growth Factor Genes in the Development of Primary Knee Osteoarthritis - Matvey Sosa-Arellano; Norma C. González-Huerta; Eugenio Morales-Hernández; Carolina Duarte-Salazar; Antonio Miranda-Duarte (Permanyer, 2022)
Background: The association of leptin (LEP) and vascular endothelial growth factor A (VEGFA) genes with the susceptibility to knee osteoarthritis (OA) has been analyzed; however, the epistasis between them has not been investigated. Objective: The objective of the study was to analyze the association of LEP and VEGFA variants and their interaction with primary knee OA in a Mexican Mestizo population. Methods: A case-control study was developed. Cases were ≥40 years, BMI ≤27 kg/m2, with primary knee OA and radiologic Grade ≥2. Controls were participants with no knee OA and a radiologic Grade <2. The rs2167270 of LEP and rs2010963 of VEGFA were genotyped. Genotypic association was tested under codominant, dominant, and recessive models. Uni- and multi-variate analyses were developed through non-conditional logistic regression. The multifactor dimensionality reduction algorithm was developed to detect epistasis. Results: Participants comprised 103 cases and 179 controls. Allelic and genotypic distributions did not show differences between the groups. Notwithstanding, a statistically significant interaction was observed between the LEP and VEGFA genes (p = 0.02) with a testing accuracy of 0.5199 and cross-validation consistency of 10/10. This interaction model confers an increased risk to knee OA (OR [95% CI] = 1.8 [1.1-2.9]). Conclusion: Interaction between LEP and VEGFA is related with genetic susceptibility to developing primary knee OA.